Effects of captive and primate-focused tourism on the gut microbiome of Tibetan macaques - Xia, Yingna; Xu, Xiaojuan; Chen, Huijuan; Yue, Ran; Xia, Dongpo; Wang, Xi; Li, Jinhua; Sun, Binghua (Frontiers in Microbiology, 2022)
Documenting the effects of anthropogenic activities on the gut microbiome of wild animals is important to their conservation practices. Captivity and ecotourism are generally considered two common anthropogenic disturbances on the health of nonhuman primates. Here, we examined the divergences of gut microbiome in different environments of Tibetan macaques. Our results showed that there were no significant differences in the alpha diversity, predominant families and genera of gut microbiomes between wild and tourist groups. However, these indexes decreased significantly in the captive individuals. In addition, the significant differences of beta diversity and community compositions between wild and tourism groups also were detected. In particular, higher potential pathogenic and predicted KEGG pathway of drug resistance (antimicrobial) were detected in the gut microbiome of individuals in captive environment. Our results indicated that living in the wild are beneficial to maintaining gut microbial diversity of Tibetan macaques, while captivity environment is harmful to the health of this macaque. Exploring ways to restore the native gut microbiome and its diversity of captive individual should pay more attention to in the future studies.